2013
DOI: 10.5120/13740-1548
|View full text |Cite
|
Sign up to set email alerts
|

Estimating a Function of Real Demand for Money in Pakistan: An Application of Bounds Testing Approach to Cointegration

Abstract: This paper attempts to model a real demand for money function of Pakistan. For this purpose we apply bounds test based cointegration technique using the time series data for the period 1973 to 2010. Our findings included three determinants: 1) real income and 2) foreign exchange contain positive relation as well as for both long run and short run dynamics they are the most significant factors of real demand for money. While we found real demand for money is negatively affected by 3) call money rate (is proxied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…After these different theories are carried out, the literature turns to investigate money demand function empirically. Baharumshah et al, 2009;Bahmani-Oskooee and Bohl, 2000;Bahmani-Oskooee and Shabsigh, 1996;Bahmani-Oskooee* and Rehman, 2005;Bhaskara and Singh, 2006;Cheong, 2007;Dreger and Wolters, 2010;Hamdi et al, 2015;Hamori and Hamori, 2008;Kjosevski, 2013;Knell and Stix, 2005;Mall, 2013;Samreth, 2008 are consider both determinant of demand function and its stability. In the African continent, a sufficient number of empirical evidence ware published in particular (Darrat, 1986;Kapingura, 2014;Kumar et al, 2013;Nchor and Adamec, 2016;Tlelima and Turner, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After these different theories are carried out, the literature turns to investigate money demand function empirically. Baharumshah et al, 2009;Bahmani-Oskooee and Bohl, 2000;Bahmani-Oskooee and Shabsigh, 1996;Bahmani-Oskooee* and Rehman, 2005;Bhaskara and Singh, 2006;Cheong, 2007;Dreger and Wolters, 2010;Hamdi et al, 2015;Hamori and Hamori, 2008;Kjosevski, 2013;Knell and Stix, 2005;Mall, 2013;Samreth, 2008 are consider both determinant of demand function and its stability. In the African continent, a sufficient number of empirical evidence ware published in particular (Darrat, 1986;Kapingura, 2014;Kumar et al, 2013;Nchor and Adamec, 2016;Tlelima and Turner, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On stability, the study reveals that demand for money in Nigeria is stable over the study period. Mall (2013) also examines the function of real demand for money in Pakistan. Annual time series data spanning the period 1973 to 2010 is employed and bounds testing approach to cointegration used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some empirical studies of demand for cash have used variable exchange rates due to its impact on the demand for real cash balances (Augustine & Shwiffm, 1993). In this regard several of studies from 1970 to 2010 have witnessed the relative importance of the variable nominal exchange rates as well as real exchange rate as determinant of money demand models in developing and developed economies (Sober, 2013). It indicated that it would be preferable to include inflation and exchange rates in economies with high inflation rates, and that the exchange rate could measure the expected rate of decline, and thus the opportunity cost of retaining the national currency versus foreign currency (Bahmani-oskooee & Shin, 2002;Akinlo, 2006;Dagher & Kovanen, 2011).…”
Section: Exchange Ratementioning
confidence: 99%